Pembangunan Karakter Mandiri Anak di PAUD Salsabila, Kota Banda Aceh - Khafidah, Wahyu (Indonesian Journal of Islamic Early Childhood Education, 2019)
The purpose of this study is to describe the teacher's efforts in building the child's independent character in PAUD Salsabila in Banda Aceh City. This type of research is descriptive qualitative research. The researcher collects data by means of observation, interviews, and documentation. The data analysis technique is done using data triangulation techniques. The efforts of teachers in building children's independent character in PAUD Salsabila in Banda Aceh City can be observed in all activities carried out by children from school to the school schedule. The results of the study indicate that the teacher seeks to build independent character in the child by 1. Greeting and answering greetings, 2. Walking politely, 3. Speaking politely. 4. Trim after completion, 5. Prepare storage and 5. Give an example.